To move or not to move? The housing preferences of a post-socialist city in the suburbanisation stage - Wiktor Błoch; Michał Mackiewicz; Mariusz Sokołowicz (Rozwój Regionalny i Polityka Regionalna)
Researchers of urban mobility patterns and residential preferences of urban dwellers increasingly inquire whether these processes are universal or place-specific. It is also interesting in the context of processes taking place in post-industrial and post-socialist cities, considering their rapid demographic and spatial transformations (e.g. the process of shrinkage, which is simultaneous with the process of suburbanization). In turn, in the context of housing mechanisms, it is interesting how much the urban life cycle coincides with the life cycle of its households. To address this question, we conducted a study based on an extensive stated preferences survey (N = 1113) from Poland’s third-largest city – Lodz. It allowed us to statistically elaborate on the determinants of the preference to move from an existing home to a new location and to what extent the physical and social environment of the properties, defined through the lenses of urban amenities, affects such decisions. We found that 56% of respondents declared that they would prefer to live in a different neighbourhood than the ones they currently live. In line with the household’s life cycle model, age was the main driving factor, while urban amenities played a minor role in determining location preferences. The youngest age group preferred to live in the city centre, while late-middle age groups preferred to move to the suburbs. Also, people living in single-family houses strongly preferred to stay in their current location, compared to those inhabiting all other types of buildings.